A case of everting ectopic ureterocele in child--controversy in the surgical treatment - Asakura, H (Hinyokika kiyo. Acta urologica Japonica, 1990)
A 4-year-old girl with the history of repeated urinary tract infections was referred from the pediatric department to our department on January, 1987. Under the diagnosis of right ectopic ureterocele of everting type with complete duplication of renal unit, the one-stage operation, that is, right hemi-nephroureterectomy with complete excision of the ureterocele and ureteral stump was carried out on January 27, 1987. Reimplantation of the orthotopic mate ureter was done because of injury to lower part of the mate ureter during operation, although reflux of the mate ureter did not exist. After the operation, the voiding symptom became better except for large residual urine volume (300 ml). In order to protect renal function, intermittent catheterization was carried out. Two years and 8 months after that operation, residual urine volume was reduced to 20 ml. Judging from the literature and our experience, if the patient is not in a severe condition, we recommend one-stage operation, that is, total correction (a single operation designed to correct abnormalities of the upper and lower urinary tract) for ectopic ureterocele in children